(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Fatal flame burn injuries remain one of the most common causes of fatalities referred to Al-Sulaimania Medico-Legal Institute in spite of many recent advances in care and management. They occupied number one of all cases which were managed medico-legally. Objective:To study, evaluate and determine the causes of death in victims of flame burn injuries. Method:The study was conducted on 221 cadavers of flame burn injuries referred to the medico-legal institute in Sulaimania province during the period between 8th of May 2008 and 7th of May 2009. Complete classical autopsy was performed on each case as well as proper laboratory investigation (CO and renal function tests). Results:Fatal flame burn injuries constituted (28%) of the total number of medico-legal mortalities during the period of the study. The highest percentage of flame burn deaths occurred during the 1st and 2nd day of burn which was related to the state of shock and primary toxemia in (46.08%) of the cases. Late deaths were due to septicemia, cumulative effects of the early cause and miscellaneous causes. Conclusion:Flame burn injuries were the most common police cases managed medico legally. The vast majority of victims died within the first ten days. Staphylococcus aureus was the most common organism isolated from wounds and blood of victims. Key words:Autopsy, flame burn, Al-Sulaimania.